Effect of fertigation and microorganisms on yield, fruit quality and foliar nutrient concentration in Hass avocado (Persea Americana Mill.) in the Tumbaco Valley-Ecuador. - Gaona Gonzaga, Juan Pablo (2025)
The cultivation of Hass avocado has increased in Ecuador due to growing international demand. To increase the productivity of this crop, we must generate information that promotes the use of environmentally friendly technologies, such as drip irrigation, fertigation, and microorganisms. In this study, the effect of fertigation and application of Trichoderma asperellum and Glomus iranicum var. tenuihypharum on yield, fruit quality, and foliar nutrient uptake was assessed in 36-week-old Hass avocado plants. The treatments were: fertigation, fertigation and microorganisms, microorganisms, and control. Production variables, fruit quality, and foliar concentrations of macronutrients (N, P, K, Ca, Mg, and S) and micronutrients (B, Fe, Zn, Cu, and Mn) were measured in two production cycles. Treatments with fertigation and application of microorganisms obtained higher averages in the evaluated variables than in the control. A trend in increasing yield was observed with the combined use of these technologies (11.33 t ha-1) about the power (8.47 t ha-1). The results of this study showed the positive effect generated by the use of fertigation and microorganisms in avocado cultivation.